2018
DOI: 10.1017/wsc.2018.38
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Mechanism of Atrazine Resistance in Waterhemp (Amaranthus tuberculatus) from Nebraska

Abstract: Resistance to atrazine (a photosystem II [PSII] inhibitor) is prevalent in waterhemp [Amaranthus tuberculatus(Moq.) J. D. Sauer] across the U.S. Midwest. Previous research suggests that target-site mutation or rapid metabolism of atrazine mediated by glutathioneS-transferase (GST) conjugation confers resistance inA. tuberculatusfrom Illinois. The distribution and mechanism of resistance to atrazine inA. tuberculatuspopulations from Nebraska (NE) are unknown. In this research we (1) evaluated the response and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 54 publications
4
29
0
Order By: Relevance
“…Enhanced herbicide metabolism via P450 enzymes was also reported in a waterhemp population resistant to HPPD-inhibitor herbicides in Nebraska 69,70 . Atrazine resistance with rapid herbicide metabolism via enhanced GST conjugation was widespread in waterhemp populations in Nebraska 54 . Although non-target-site glyphosate resistance with metabolism in plants is relatively rare 71 , non-target-site resistance with reduced glyphosate translocation was identified in waterhemp biotypes in Mississippi 72 .…”
Section: Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhanced herbicide metabolism via P450 enzymes was also reported in a waterhemp population resistant to HPPD-inhibitor herbicides in Nebraska 69,70 . Atrazine resistance with rapid herbicide metabolism via enhanced GST conjugation was widespread in waterhemp populations in Nebraska 54 . Although non-target-site glyphosate resistance with metabolism in plants is relatively rare 71 , non-target-site resistance with reduced glyphosate translocation was identified in waterhemp biotypes in Mississippi 72 .…”
Section: Populationmentioning
confidence: 99%
“…Both are obligate outcrossing dioecious weed species with a fast growth habitat, extended emergence window, and prolific seed production with high genetic plasticity which pose a challenge to their management 37-44 . Numerous Palmer amaranth and waterhemp populations have evolved resistance to herbicides that target 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS), 4-hydroxyphenylpyruvate dioxygenase (HPPD), photosystem II, protoporphyrinogen oxidase (PPO), auxin receptors, microtubule assembly, and acetolacte synthase (ALS) in the US 15,17,[45][46][47][48][49][50][51][52][53][54] . Moreover, pollen mediated gene flow has been reported as a major contributor to herbicide resistance dissemination in Palmer amaranth and waterhemp in the US Midwest 55,56 .Although controlling weed populations on field margins and ditches is considered a best management practice to delay herbicide resistance evolution, these weed populations are often neglected in agricultural landscapes [15][16][17]29 .…”
mentioning
confidence: 99%
“…NTSR to PS-II inhibitors have been documented in annual bluegrass [63], common ragweed [64], common waterhemp [65,66], Palmer amaranth [67,68], and wild radish [62]. In the majority of these cases, the metabolism of PS-II inhibitors was catalyzed by the enhanced activity of GST enzymes [69] and/or CYP450 enzymes [70].…”
Section: Known Ntsr Mechanisms In Weed Species For Different Herbimentioning
confidence: 99%
“…For example, atrazine-resistant Palmer amaranth from Kansas was found to conjugate atrazine 24 times faster than the susceptible plants via enhanced GST-activity [67]. Similarly, the enhanced metabolism of atrazine was found in two common waterhemp populations from Illinois [10] and Nebraska [65]. In the atrazine-resistant common waterhemp from Nebraska, at 6 HAT, approximately 92% of the atrazine was found to be conjugated by GSTs, whereas 92% of atrazine was still retained as a parent compound in susceptible plants [65].…”
Section: Known Ntsr Mechanisms In Weed Species For Different Herbimentioning
confidence: 99%
“…The ED 50 value for the NER biotype was higher (P < 0.05) than that of the susceptible biotype (S1) (data not shown), and based on the ED 50 values, the NER biotype was 7-fold resistant to atrazine compared with the S1 biotype. Atrazine-resistant A. tuberculatus in Nebraska was first reported in 1990 (Anderson et al 1996), and A. tuberculatus resistant to atrazine applied POST is widespread in Nebraska: a 2014 survey of 85 fields in eastern Nebraska revealed that atrazine-resistant A. tuberculatus was present in 73% of all fields surveyed (Vennapusa et al 2018). The occurrence of atrazine-resistant A. tuberculatus with a high level of resistance is also widespread in other states in the Midwest (Heap 2019b): for example, a recent report suggested that a multiple herbicide-resistant biotype from Missouri showed 7-to 19-fold resistance to atrazine (Shergill et al 2018a).…”
Section: Regression Parameters (±Sem)mentioning
confidence: 99%